Group-based physical activity trajectories in children transitioning from elementary to high school - Russell R. Pate; Michaela A. Schenkelberg; Marsha Dowda; Kerry L. McIver (BMC, 2019)
Abstract Background Physical activity has been observed repeatedly to decline as children transition into adolescence; however, few studies have explored the possibility that sub-groups of children experience unique patterns of change during this transition. The purpose of this longitudinal study was to examine the physical activity trajectories in clusters of youth transitioning from 5th to 11th grade. Methods Participants (n = 652) were recruited as 5th graders (ages 10-12 years) from elementary schools (n = 21) in two school districts. Demographic, anthropometric, and physical activity data were collected once per year when children were in 5th, 6th, 7th, 9th, and 11th grades. Children wore accelerometers for 7 consecutive days. Group-based trajectory modeling statistical techniques were applied to identify patterns of physical activity trajectories. Posterior probabilities confirmed participants' membership in their respective group. Results Three distinct physical activity trajectories were identified. Group 1 (n = 27) remained highly active over time, and physical activity increased from ages 14 to 16 years. Group 2 (n = 365) was active at baseline, but activity declined and remained low as group members aged. Group 3 (n = 260) had the lowest levels of physical activity at all ages, and activity declined from ages 10 to 16 years. Conclusions While most children experienced a decline in physical activity as they transitioned into high school, some remained highly active and increased their level of physical activity. Future studies should test physical activity interventions for youth that are tailored for age-related trajectory groups.